Estimated Output, Price, Interest Rate, and Exchange Rate Linkages among Countries - Fair, Ray C. (Journal of Political Economy, 1982)
This article provides quantitative estimates from an econometric model of the output, price, interest rate, and exchange rate linkages among a number of countries. The linkages are examined by changing various policy variables and observing the resulting changes in the endogenous variable. The model is also used to estimate what is called the "exchanging rate effect" on inflation. One of the ways in which monetary and fiscal policies may affect a country's inflation rate is by first influencing its exchange rate, which in turn influences import prices, which in turn influence domestic prices. The model allows this exchange rate effect on inflation to be estimated.